(untitled) (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1993)
lt is likely that the external and internal differentiation of high level qualified service labor will have consequences for the employees concerned: For chances in their responsibilities, their organizational reference, their position in the market, but also for their professionally endemic thinking about the nature of ’technical progress’. lt is assumed that changes observable within engineering services reflect the development of highly qualified white collar labor in industrial organizations in general. If the ’service character’ of these occupations is more and more typical for modern qualified work, the potential contradictions between orientation towards the market and orientation towards scientifically based professional ’identity’ will grow - or end in an new service-oriented professional self-image which is highly functional for the interests of the modern capitalist enterprise. The crucial question will be: Which responses will enterprise policies on the one hand, unions on the other hand develop to integrale or represent the (career-oriented) interests of the majority, but also the interests of a (critical) minority of highly qualified employees? Members of this minority suffer under the strains between their organizational function in private enterprise and their professional (or personal) values on questions like the environment or technical and social progress. lt will - among other factors - depend on the responses to those aspirations whether the German unions will be able to integrale at least the critical, thus far unorganized potential of highly qualified professions. As a first step, the unions should address the scientifically educated employees simultaneously as experts and important partners of dialogue within ’risk society’.